Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak. Issue 8 (27th May 2018) - Downes, J K; Yatabe, T; Marcos‐Lopez, M; Rodger, H D; MacCarthy, E; O'Connor, I; Collins, E; Ruane, N M
Abstract: Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co‐infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co‐infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii, Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus (SGPV) during a longitudinal study on a marine Atlantic salmon farm. Real‐time PCR was used to determine the presence and sequential infection patterns of these pathogens on gill samples collected from stocking until harvest. A number of multilevel models were used to determine the effect of these putative pathogens on gill health (measured as gill histopathology score), while adjusting for the effect of water temperature and time since the last freshwater treatment. Results indicate that between 12 and 16 weeks post‐seawater transfer (wpst), colonization of the gills by all pathogens had commenced and by week 16 of marine production each of the pathogens had been detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected during this study. Detections of T. maritimum were found to be significantly correlated with temperature showing distinct seasonality. Salmon gill poxvirus was found to be highly sporadic and detected in the first sampling point, suggesting a carryover from the freshwater stage of production. Finally, the model results indicated no clear effect between any of the pathogens. Additionally, the models showed that the only variable which had a consistent effect on the histology score was N. perurans .